As mestras do barro: a arte das louceiras no semiárido paraibano - Leite, Ana Paula Gonçalves (2019)
One of the most prosperous spaces for ethno pedological and ecological studies is the use of soils for handicraft activities. Several Brazilian States record a large production of clay objects, however this culture has not received appropriate attention from public management. Thus, the goal of this research is to register and analyze the knowledge of crockery maker women in the community Ligeiro de Baixo, Serra Branca, Paraíba, Brasil, about the use of soil for commercial purposes, identifying the public policies of support and incentive, its impact for the crockery makers and difficulties in the collection, production and marketing process. Data were collected by direct observation, semi structured interview and informal dialogue. Six crockery makers were interviewed directly. Although retaining the knowledge of the most experienced, the new generation shows no interest in the continuity of the activity, mainly due to cultural, political-social and economic devaluation. More participatory management becomes urgent, as well as actions in education and culture, for the awakening of society and the preservation of this traditional knowledge that translates the whole history of a people.